Zika-virus-infected human full-term placental explants display pro-inflammatory responses and undergo apoptosis - Ribeiro, Milene Rocha [UNESP]; Moreli, Jusciele Brogin; Marques, Rafael Elias; Papa, Michelle Premazzi; Meuren, Lana Monteiro; Rahal, Paula [UNESP]; de Arruda, Luciana Barros; Oliani, Antonio Helio; Oliani, Denise Cristina Mós Vaz; Oliani, Sonia Maria [UNESP]; Narayanan, Aarthi; Nogueira, Maurício Lacerda (Springer Nature, 2018)
Zika virus (ZIKV) is a flavivirus that has been highly correlated with the development of neurological disorders and other malformations in newborns and stillborn fetuses after congenital infection. This association is supported by the presence of ZIKV in the fetal brain and amniotic fluid, and findings suggest that infection of the placental barrier is a critical step for fetal ZIKV infection in utero. Therefore, relevant models to investigate the interaction between ZIKV and placental tissues are essential for understanding the pathogenesis of Zika syndrome. In this report, we demonstrate that explant tissue from full-term human placentas sustains a productive ZIKV infection, though the results depend on the strain. Viral infection was found to be associated with pro-inflammatory cytokine expression and apoptosis of the infected tissue, and these findings confirm that placental explants are targets of ZIKV replication. We propose that human placental explants are useful as a model for studying ZIKV infection ex vivo.